Efecto del tipo de apoyo de las cadenas de amarre en el análisis y diseño de las cimentaciones de edificaciones - Castelo Merino, Ronny Alexander (2024)
The research analyzes tie-down chains under different types of support and their influence on foundation design. Supports such as natural soil (NS), vibro-compacted soil (VC), compacted granular material over soil (MG), and cyclopean concrete continuous footing (HC) were explored, considering different boundary conditions. A comparative statistical analysis was conducted to assess the influence of these supports on aspects such as soil pressures, foundation self-weight, chain deflections, flexural moments, shear forces in chains and tie beams, and chain, beam, and pile design. The objective was to study chain behavior under these supports through modeling in SAP2000 and interpreting the soil-structure interaction. Under a quantitative methodology, 20 structural models were created for each support type and boundary condition. The results highlight that chain behavior varies depending on the type of support, with cyclopean concrete continuous footing being the most beneficial, especially regarding savings in structural steel. This thesis provides a detailed understanding of the impact of tie-down chains under different support types, emphasizing the benefits derived from such supports. Further research is recommended to consider architectural layouts, focusing on the presence of walls over the chain and conducting a unit price analysis to discern differences in the application of enhancements under the chain.